Accelerating functional gene discovery in osteoarthritis - Natalie C. Butterfield (Nature Portfolio, 2021)
Osteoarthritis is a chronic, heritable disease with no available treatment. Here, the authors show that a validated, rapid-throughput joint phenotyping pipeline detects osteoarthritis in the mouse knee following surgical provocation, in aging and after single gene deletion or point mutation.